Does green credit promote real economic development? Dual empirical evidence of scale and efficiency. - Song Jiang; Xiaoqin Yuan (PLoS ONE)
Green credit has emerged as a new engine for economic transformation and a core driving force behind high-quality development. By using panel data from 30 provinces in China, this paper comprehensively examines the influence of green credit on the real economy. The research findings suggest that green credit has a significantly positive effect on the scale of the real economy but a significantly negative effect on the efficiency of the real economy. In addition, we construct instrumental variables for green credit to address endogeneity problems, The results are tested by rigorous robustness checks. The mechanism analysis reveals that green credit mainly exerts its influence by promoting the optimization of the industrial structure, reducing energy consumption and reducing green innovation. The reduction of green innovation patents due to green credit undoubtedly reflects significant obstacles in the current process of promoting economic transformation through green credit in China. This study provides a theoretical framework for understanding the macro-level implications of green credit. Moreover, it offers valuable insights for formulating policies targeting the financial services sector of the real economy.